Step-by-step explanation:
42 is your answer according to bodmas
Answer:
f(-3) = 21
g(3) = 69
Step-by-step explanation:
We have been given the following functions;
f(x) = –6x + 3
g(x) = 3x + 21x–3.
To find f(-3) , we simply substitute x = -3 in the function of f(x);
f(-3) = -6(-3) + 3
= 21
To find g(3) , substitute x = 3 in the function of g(x);
g(3) = 3(3) +21(3) - 3
= 69
Step-by-step explanation:
height= 4b
length = 2 + b
volume = 60in³
or, l ×b × h = 60in³
or, (2+b) × b × 4b = 60in³
or, 4b²(2+b) = 60in³
or, 8b² + 4b³ = 60
or, 2b² + b³ = 15
or, b³ + 2b² -15= 0
b= 1.95
l= 2+1.95=3.95
h= 4×1.95 = 7.8
0.5=0.85^x taking the natural log of both sides...
ln0.5=x ln0.85
x=ln0.5/(ln0.85)
x≈4.265
Then:
f=20000(0.85)^(4.265)
f=$10000.00 to nearest dollar